2008
DOI: 10.1016/j.bbmt.2008.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation from Matched Siblings Using Once-Daily Intravenous Busulfan/Fludarabine with Thymoglobulin: A Myeloablative Regimen with Low Nonrelapse Mortality in All But Older Patients with High-Risk Disease

Abstract: Two hundred patients received hematopoietic stem cell transplantation (HSCT) from matched sibling donors (MSD) after myeloablative conditioning including fludarabine (Flu) and once-daily intravenous busulfan (Bu). Thymoglobulin (TG) was added to methotexate (MTX) and cyclosporine (CsA) as graft-versus-host disease (GVHD) prophylaxis. For low-risk (acute leukemia CR1/CR2, CML CP1) patients projected 5-year nonrelapse mortality (NRM) and overall survival (OS) were 4% and 76% for those Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
28
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 32 publications
7
28
0
1
Order By: Relevance
“…Additional studies evaluating BU were reviewed but did not report on cutaneous toxicity. 2,3,5,[7][8][9][10][11][12][13][14] Toxic erythema of chemotherapy after high-dose BU TL Parker et al development of erosions and desquamation may be the first sign of TEC; the former may be misdiagnosed as herpetic viral infections. Lastly, the duration of the cutaneous toxicity may be weeks and to date, we have found no specific therapy that alters the clinical course.…”
Section: Study (Year)mentioning
confidence: 99%
“…Additional studies evaluating BU were reviewed but did not report on cutaneous toxicity. 2,3,5,[7][8][9][10][11][12][13][14] Toxic erythema of chemotherapy after high-dose BU TL Parker et al development of erosions and desquamation may be the first sign of TEC; the former may be misdiagnosed as herpetic viral infections. Lastly, the duration of the cutaneous toxicity may be weeks and to date, we have found no specific therapy that alters the clinical course.…”
Section: Study (Year)mentioning
confidence: 99%
“…The usual conditioning regimen during the study period was fludarabine (250 mg/m 2 ), busulfan (;12.8 mg/kg IV, pharmacokinetically adjusted), and antithymocyte globulin (Thymoglobulin; Sanofi, Paris, France; 4.5 mg/kg), 22 with or without total body irradiation (4 Gy). 23 Additional GVHD prophylaxis was provided as methotrexate (days 1, 3, 6, 11) and cyclosporine (until 3-6 months post-HCT).…”
Section: Transplantationmentioning
confidence: 99%
“…In one study, NRM after BuFlu conditioning was reduced, but older patients had more GVHD-related deaths than younger ones. 41 Retrospective comparisons of different conditioning regimens in patients with aged over 55 years suggested improved long-term outcome with BuFlu over BuCy in one study 21 while the NRM with BuFlu was similar to that reported with RIC regimens in another. 22 In this study, we evaluated the BuFlu regimen in a homogeneous series of patients with AML or MDS receiving HSCT from HLA-identical matched-sibling donors and uniform GVHD prophylaxis reducing the impact of other types of diseases and donors or prophylactic procedures.…”
Section: Discussionmentioning
confidence: 93%